Histone Lysine Demethylase JMJD2D/KDM4D and Family Members Mediate Effects of Chronic Social Defeat Stress on Mouse Hippocampal Neurogenesis and Mood Disorders - Swati Maitra; Nitin Khandelwal; Scherazad Kootar; Pooja Sant; Salil S. Pathak; Sujatha Reddy; Annapoorna P. K.; Upadhyayula Suryanarayana Murty; Sumana Chakravarty; Arvind Kumar (Brain Sciences, 2020)
Depression, anxiety and related mood disorders are major psychiatric illnesses worldwide, and chronic stress appears to be one of the primary underlying causes. Therapeutics to treat these debilitating disorders without a relapse are limited due to the incomplete molecular understanding of their etiopathology. In addition to the well-studied genetic component, research in the past two decades has implicated diverse epigenetic mechanisms in mediating the negative effects of chronic stressful events on neural circuits. This includes the cognitive circuitry, where the dynamic hippocampal dentate gyrus (DG) neurogenesis gets affected in depression and related affective disorders. Most of these epigenetic studies have focused on the impact of acetylation/deacetylation and methylation of several histone lysine residues on neural gene expression. However, there is a dearth of investigation into the role of demethylation of these lysine residues in chronic stress-induced changes in neurogenesis that results in altered behaviour. Here, using the chronic social defeat stress (CSDS) paradigm to induce depression and anxiety in C57BL/6 mice and ex vivo DG neural stem/progenitor cell (NSCs/NPCs) culture we show the role of the members of the JMJD2/KDM4 family of histone lysine demethylases (KDMs) in mediating stress-induced changes in DG neurogenesis and mood disorders. The study suggests a critical role of JMJD2D in DG neurogenesis. Altered enrichment of JMJD2D on the promoters of Id2 (inhibitor of differentiation 2) and Sox2 (SRY-Box Transcription Factor 2) was observed during proliferation and differentiation of NSCs/NPCs obtained from the DG. This would affect the demethylation of repressive epigenetic mark H3K9, thus activating or repressing these and possibly other genes involved in regulating proliferation and differentiation of DG NSCs/NPCs. Treatment of the NSCs/NPCs culture with Dimethyloxallyl Glycine (DMOG), an inhibitor of JMJDs, led to attenuation in their proliferation capacity. Additionally, systemic administration of DMOG in mice for 10 days induced depression-like and anxiety-like phenotype without any stress exposure.